An Adaptive CBPR Approach to Create Weight Management Materials for a School-Based Health Center Intervention - Andrew L. Sussman; Carolyn Montoya; Olaf Werder; Sally Davis; Nina Wallerstein; Alberta S. Kong (Journal of Obesity)
Purpose. From our previous clinical work with overweight/obese youth, we identified the need for research to create an effective weight management intervention to address the growing prevalence of adolescent metabolic syndrome. Formative assessment through an adaptive community-based participatory research (CBPR) approach was conducted toward the development of a nutritional and physical activity (DVD) and clinician toolkit for a school-based health center (SBHC) weight management intervention. Methods. We first conducted parent and adolescent interviews on views and experiences about obesity while convening a community advisory council (CAC) recruited from two participating urban New Mexico high schools. Thematic findings from the interviews were analyzed with the CAC to develop culturally and developmentally appropriate intervention materials. Results. Themes from the parent and adolescent interviews included general barriers/challenges, factors influencing motivation, and change facilitators. The CAC and university-based research team reached consensus on the final content of nutrition and physical activity topics to produce a DVD and clinician toolkit through six monthly sessions. These materials used in the SBHC intervention resulted in a greater reduction of body mass index when compared to adolescents receiving standard care. Conclusions. Formative assessment using an adaptive CBPR approach resulted in the creation of culturally and age appropriate weight reduction materials that were acceptable to study participants. This trial is registered with ClinicalTrials.gov NCT00841334.